Key Role of Staphylococcal Fibronectin-Binding Proteins During the Initial Stage of Staphylococcus aureus Keratitis in Humans - Maurin, Corantin; Courrier, Emilie; He, Zhiguo; Rigaill, Josselin; Josse, Jérôme; Laurent, Frédéric; Gain, Philippe; Thuret, Gilles; Verhoeven, Paul O. (Frontiers in Cellular and Infection Microbiology, 2021)
Objectives Staphylococcus aureus is one of the main causes of bacterial keratitis in humans. This study was aimed at investigating the mechanisms of S. aureus adhesion to the human corneal epithelium involved during the initial stage of infectious keratitis. Methods Human corneas stored in a specific active storage machine that restores a normal pluristratified epithelium were used to assess S. aureus adhesion level to intact and injured tissues using immunostaining. S. aureus adhesion to immobilized fibronectin was measured in microtiter plate. Internalization of S. aureus clinical isolates recovered from keratitis was assessed on human corneal epithelial HCE-2 cells. Results Superficial corneal injury unmasked fibronectin molecules expressed within the human corneal epithelium. S. aureus adhesion level was increased by 117-fold in the area of injured epithelium (p < 0.0001). The deletion of staphylococcal fnbA/B genes decreased by 71% the adhesion level to immobilized fibronectin (p < 0.001). The deletion of fnbA/B genes and the incubation of the corneas with anti-fibronectin blocking antibodies prior to the infection significantly reduced the S. aureus adhesion level to injured corneal epithelium (p < 0.001). Finally, S. aureus clinical isolates triggered its internalization in human corneal epithelial cells as efficiently as the 8325-4 wt. Conclusion S. aureus was almost unable to bind the intact corneal epithelium, whereas a superficial epithelial injury of the corneal epithelium strongly increased S. aureus adhesion, which is mainly driven by the interaction between staphylococcal fibronectin-binding proteins and unmasked fibronectin molecules located underneath the most superficial layer of the corneal epithelium.